The Effect of Sex Discordance on Blood Transfusion Reactions - Mohammad Eini; Haniyeh Dadaie- Joushagani; Ebrahim Miri-Moghaddam (Iranian Society of Pathology, 2022)
One of the most important ways to prevent blood transfusion reactions is to choose a suitable donor. Donated blood bags are checked at the time of administration for infectious agents and the compatibility of blood groups between the donor and the recipient. However, gender mismatch is ignored, which can cause complications following injection.